Radiotherapy Management of Locally Advanced Cervical Cancer during the COVID-19 Era: A Single Centre Report on Treatment Approach, Brachytherapy Fractionation and Timing - Valeria Chiofalo; Jacopo Di Muzio; Cristiano Grossi; Francesco Olivero; Andrea Peruzzo; Eugenia Madon; Anna Mussano; Umberto Ricardi (IMR Press, 2022)
Background: The COVID-19 pandemic had a catastrophic impact on healthcare. Keeping an optimal cancer care routine has been challenging. For cervical cancer (CC) patients external beam radiotherapy (EBRT) and brachytherapy (BT) are key elements for radical treatment. Oncological treatment delays have represented a major issue during the pandemic. Overall treatment time (OTT) is a well-known prognostic factor for CC. Thus, we decided to evaluate radiotherapy timing and modalities, and OTT trends for locally advanced cervical cancer (LACC) patients treated at our center during the Pandemic. Methods: We retrospectively collected and analyzed data of patients treated for LACC at our Center, (Department of Oncology, Radiation Oncology, S.Anna Hospital, Turin, Italy), during the COVID-19 pandemic. Results: Between March 2020 and March 2022, 36 patients were treated. All patients underwent EBRT (median pelvic dose 48 Gray (Gy)). Concurrent chemotherapy (ChT) was administered in 31/36 patients. High Dose Rate (HDR) BT boost was delivered to 32/36 patients. BT schedules adopted were: 28 Gy in 4 fractions (18 cases, 56.2%), 26 Gy in 4 fractions (5 cases, 15.6%), 21 Gy in 3 fractions (4 cases, 12.5%), 18 Gy in 3 fractions (3 cases, 9.3%), 24 Gy in 4 fractions (one case, 3.2%), 12 Gy in 2 fractions plus 11 Gy in 2 fractions (one case, 3.2%). Most of the patients (25/32, 78.1%) received one fraction per week; 6 patients (18.1%) 2 fractions per week and one patient 3 fractions per week. Median OTT was 74 days (57-99). The median interval from EBRT to HDR-BT was 14 days (6-54). Four patients tested positive for COVID-19 between EBRT and BT. At a median follow-up of 10.7 months (range 1.8-20.3), a complete response was obtained in 25 patients (69.5%), a partial response in 8 cases (22.2%), and a disease progression in two patients (5.5%). Conclusions: in terms of radiotherapy management of LACC, brachytherapy resulted as the most affected by the restrictions due to the pandemic. We adopted different schedules and fractionations to optimize the resources available and to keep providing an optimal care. A be-weekly fractionation emerged as a promising option for LACC during the pandemic, with a good toxicity profile.